CALCULO DE DOSIS EN BRAQUITERAPIA OCULAR CON HILOS DE Ir- 192 UTILIZANDO LA INTEGRAL DE SIEVERT Y CORREGIDA POR ATENUACIÓN Y DISPERSIÓN CON LOS POLINOMIOS DE MEISBERG - Bemui de V., M. Giselle (2005)
The ocular brachytherapy, sorne times the only altemative to conserve the visual organ in patients of ocular cancer, comes making in the Instituto Nacional de Enfermedades Neoplasicas using threads of Ir 192; which, are placed in radial form on the inner surface of a spherical gold cap of 18 K; the cap remains in the eye until reaching the dose prescribed by the doctor. The primary target of this work is to be able to calculate of a correct and practica!way the time that must last the treatment of ocular brachytherapy to reach the dose prescribed by the doctor. In order to reach this objective, it is use the integral of Sievert corrected by attenuation effects and dispersion (polynomials of Meisberg); calculating it by the method of Simpson. In the calculations using integral of Sievert the dispersion produced by the gold cap and the variation of the constant of dose rate with the distance is not taken into account. The calculations by means of integral of Sievert are compared with the obtained ones using the simulation code Monte Cario Penélope, where it is observed that both calculation are agree to distances greater than 2mm from the surface cap.